STUDI LITERATUR REVIEW FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN INTERNET FINANCIAL REPORTING (IFR) SEBAGAI VOLUNTARY DISCLOSURE - Rina Marliana; Medina Almunawwaroh (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2018)
At this time utilizing the support of the internet and the digital world as a place for interaction and transactions has been widely applied by many people. Using the internet allows information to be disseminated throughout the world and increases the availability of financial information in particular, thereby encouraging investment. Although the phenomenon of Internet Financial Reporting (IFR) is growing, there are still many companies that have not implemented Internet Financial Reporting (IFR). The results of this study indicate that the application of Internet Financial Reporting (IFR) in a company there are factors that influence it. The purpose of this study is to describe the factors that influence the application of Internet Financial Reporting (IFR) as voluntary disclosure. The research was conducted through a literature study by collecting articles from online journals related to factors that influence the application of Internet Financial Reporting (IFR). The results of the study indicate that the factors that influence the implementation of Internet Financial Reporting (IFR) are company size, profitability, type of industry, leverage, outside ownership, systematic risk and Good Corporate Governance.